Colisiones arquitectónicas (2020)
Cities are made up of a large number of spatial elements, each one with different urban dynamics that must be studied carefully and precisely as a whole and not, as different isolated pieces in the plane; rather as a series of elements that organized and read as a group are the shapers of a city. At first, the site of interest was analyzed as a place full of opportunities, problems and concrete benefits. However, each piece is isolated from one another, with its own incorruptible dynamics and surrounded by tangible and intangible limits that formed a divided city. That is why the objective of the project is focused on retaking these isolated pieces of the city and commissioning them within a new urban network superimposed on the existing one, thus creating spaces of symbiosis with elements directly related to each other, which forges in turn, new urban nodes and transition spaces within them that mix the particularities of a complex system, together with the diversity of the different components of the existing and new urban structure.